The prospect of liquid-based dye sensitized solar cells (DSSCs): A Comparative Review - Selan, Odi Th. E. (Universitas Nusa Cendana, 2020)
Energy demands including electricity consumptions have been increasing rapidly inrecent years. Silicon solar cells, the most highly used cells dominating global markets,contribute significantly in providing sustainable form of energy. More importantly, itpromisingly enables people especially in rural and remote areas to have access to electricitythat could potentially stimulate rural development. However, this energy platform still suffersfor high production and maintenance costs and the use of hazardous materials. Softinterface solar cells seems to take advantage over silicon solar cell design but review articlesexplaining the advantages of this new approach are rarely found. This article provides ageneral overview about an emerging solar cell based on liquid│liquid junction interface fromchemistry perspective, highlights its benefits over silicon based solar cells and argues thatthis technology is a potential substitute for the existing ones by focusing specifically on theissues of costs, environmental impacts, electron transfer and fabrication techniques.